PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI MIA 1 MAN 3 KOTA PEKANBARU - Noveli, Sonya; Saragih, Sehatta; Solfitri, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The learning process is seen as one of the main factors that influence learning outcomes so that this research aims to improve learning process and students’ mathematics learning achievement by applying Discovery Learning model. This research is a classroom action research with two cycles. The research instruments used are mathematical learning instruments (Syllabus, Lesson Plans, and Activity Sheets) and data collecting instruments (Observation Sheets and Students Mathematic Tests). Data collection techniques in this research used are observation techniques and test techniques. The observation sheets were analyzed in qualitative desciptive, while the students Mathematic tests were analyzed in quantitative descriptive. Subject of this research are students of XI MIA 1 MAN 3 Kota Pekanbaru in second semester of academic year 2018/2019, which consist of 30 students. Based on the analysis of students and teacher activities after implementation of the Discovery Learning model, it can be concluded that there is an improvement of learning process. On knowledge competence, the number of students who can reach KKM in Cycle I is 26,67% and 63,33% in Cycle II. On skill competence, the number of students who can reach KKM in Cycle I with percentage 26,67% and 43,33% in Cycle II. Based on the result, it can be concluded that the implementation of Discovery Learning model can improve the learning process and the students’ mathematics learning outcomes in class of XI MIA 1 MAN 3 Kota Pekanbaru.Key Words : Mathematics Learning Achievement, Discovery Learning Model, Classroom Action Research